Vocação: uma perspectiva junguiana - A orientação vocacional na clínica junguiana - Molineiro, Maria Lygia de Carvalho Alli (2007)
This present study aims at understanding the vocational thematic under the perspective of the Analytic Psychology and investigating the specification of the Junguian approach on its theorical dimension and clinical practice concerning Vocational Guidance. It presents a theoretical study along with the principles which give the bases to the understanding of the Analytic Psychology about the vocational concept, including it in the list of the different theoretical perspectives on the subject. The Junguian Psychology understands that the development of the personality implies the free and conscient choice of a personal path, which includes the professional dimension, in harmony with the Self, the wholeness archetype, and the ordenating axle of the conscient and unconscient psyche. This dissertation emphasizes the comprehension of the Junguian Psychology about adolescence as a stage of development, a phase of changes and transformations and a life period when the personal and professional choices begin to be taken and considers it as a step in the individuation process. It studies the issue of vocation in the Ancient Greece, as a reference of the western culture, and debates the issue of adolescence and of vocational choice in contemporary times. It presents a clinic illustration sample of Vocational Guidance in a Junguian perspective